Translucency, color, and hardness of 3D-printed provisional restorations - Hayriye Yasemin Yay Kuscu; Zuhal Gorus (Scientific Reports)
Abstract This in vitro study investigates effects of different thicknesses (1 mm, 2 mm, 3 mm) and post-curing durations (20 and 25 min) on the translucency parameters (TP), color differences, and microhardness (HV) of NextDent 3D-printed provisional restorations. Fifty-four disk specimens (10 mm diameter) in three thicknesses (1 mm, 2 mm, 3 mm) were post-cured for 20–25 min, forming six groups (n = 9 per group). Color measurements were taken against white and black backgrounds to calculate TP and color differences. Microhardness was measured using a Vickers hardness tester (100 g load, 10 s). Data were analyzed with two-way ANOVA and pairwise comparisons were performed with LSD post-hoc tests (significance level: 0.05). Thickness significantly influenced TP, with 1 mm specimens showing the highest values (P < .05). Post-curing duration did not significantly affect TP or HV (P > .05). Vickers hardness was higher in 1 mm specimens than thicker samples (P < .05). No significant interaction was found between thickness and post-curing time. Thickness affects translucency and hardness in 3D-printed restorations, while post-curing times of 20 and 25 min had minimal impact. Clinicians should consider thickness based on esthetic and functional needs. Future studies should explore broader post-curing times and additional material properties.